The risk of carotid stenosis in head and neck cancer patients after radiation therapy. (May 2018) - Carpenter, David J.; Mowery, Yvonne M.; Broadwater, Gloria; Rodrigues, Anna; Wisdom, Amy J.; Dorth, Jennifer A.; Patel, Pretesh R.; Shortell, Cynthia K.; Clough, Robert; Brizel, David M.
Graphical abstract: Highlights: Carotid stenosis incidence was high, rising over time after head and neck radiation. Diabetes was predictive of time to carotid stenosis on multivariate analysis. Carotid dose parameters were not significantly associated with carotid stenosis. Abstract: Objectives: Head and neck radiotherapy (RT) is a risk factor for cerebrovascular disease. We performed a retrospective cohort study to evaluate carotid artery stenosis (CAS) incidence in head and neck cancer (HNC) patients undergoing RT, characterizing associated risk factors. Materials and methods: Records were retrospectively reviewed for HNC patients undergoing carotid ultrasound screening after definitive or adjuvant RT between January 2000 and May 2016. CAS was defined as ≥50% stenosis on imaging, stroke, or transient ischemic attack. Actuarial CAS rates were calculated by Kaplan-Meier method. Univariate and multivariate analyses predicted CAS risk based on carotid dosimetric and clinical parameters. Results: 366 patients met inclusion criteria. Median time from RT completion to last follow-up was 4.1 yr. Actuarial risk for CAS was 29% (95% CI 22–36%) at 8 years. Univariate analysis showed that smoking (HR 1.7; 95% CI 1.1–2.7), hyperlipidemia (HR 1.6; 95% CI 1.03–2.6), diabetes (HR 2.8; 95% CI 1.6–4.8), coronary artery disease (HR 2.4; 95% CI 1.4–4.2), and peripheral artery disease (HR 3.6; 95% CI 1.1–11.6) were significantly associated with increased CAS. In multivariate analysis, diabetes was predictive of time to CAS (HR 1.9; 95% CI 1.1–3.4). Carotid dose parameters were not significantly associated with CAS. Conclusions: CAS incidence is high after head and neck radiotherapy, gradually rising over time. No clear dose-response effect between carotid dose and CAS was identified for HNC patients. Carotid artery screening and preventative strategies should be employed in this high-risk patient population.